Órbitas nas vizinhanças da inclinação crítica - Rodriguez Castilla, Alberto Enrique [UNIFESP] (2020)
This work consists of analyzing the stability of the orbits of space satellites orbiting satellites planetariums in the neighborhoods of critical inclinations. Such analysis mainly involves the study of the problem of the two bodies, of the Lagrange Planetary equations, of the gravitational potential of a planet, of the equations of motion in the Hamiltonian form and of the Lyapunov's stability. We will see some results on the behavior of orbits in the neighborhood of a critical inclination and the importance of the C₂₂ coecient when studying the Lyapunov stability of the solution of the system of equations of motion, in the Hamiltonian form, with specic initial conditions, when C₂₂=0 and when C₂₂≠0.